THE PERCEPTION OF ADOPTING AN INFORMATION TECHNOLOGY INNOVATION ON RURAL BANKS OWNED BY THE LOCAL GOVERNMENT - Puspitasari, Elen; Srimindarti, Ceacilia (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
The performance of rural banks owned by the local government showed progress veryproud. Therefore, policies and strategies for the future development of rural banks directedin accordance with the fundamental characteristics of rural banks, which is rural banks ascommunity banks are healthy, strong, productive and spread throughout Indonesia and focusedin the provision of financial services the small, micro and medium enterprises (SME’s) andlocal communities, especially in rural areas.The purpose of this study was to find out whichvariables are to be determinant to measure the user’s perceptions of adopting an informationtechnology (IT) innovation on the rural banks owned by local government. Respondents in this study were employees as user’s adoption of IT on rural banks. Data obtained from respondents’ answers to the questionnaire. The factors that influence adopting an information technologyinnovation, which is voluntariness, relative advantage, compatibility, image, ease of use, resultdemonstrability, visibility, trial ability, and facilitating conditions to be determined by principlecomponent analysis under Factor Analysis Techniques.The adoption of information technologiesby individuals and organizations has been an area of substantial research to extend informationsystem. One of the important strategies that need to be done by the rural banks in order toincrease competitiveness and outreach is empowering of supporting infrastructure industriesowned by rural banks effectively, especially in information technology.